Production Research and Risk Factor Analysis of Transfusion and Infusion Warmer Based on Real-World Data - Hongfeng BI; Yonggang WANG; Zhendong WANG; Yuan FU; Huifang NIU (Zhongguo yiliao qixie zazhi)
Objective To investigate the transfusion and infusion warmer manufacturers, combine the use failures to analyze adverse events, and provide support for enterprise risk management and clinical safe use. MethodsThe sentinels from 7 manufacturing enterprises and 11 medical institutions that participated in Shandong Province’s key monitoring program during the "14th Five-Year Plan" period were targeted. This was done by understanding the equipment’s principles, structures, and quality control. Additionally, real-world data from January 2019 to December 2023 were collected to count adverse events. ResultsDuring production, there are risks in switching power supply stability and solder joint firmness. Fifteen kinds of faults occurred during use, and common faults such as inability to heat, unable to turn on the machine, and bubbles in the infusion tube accounted for more than 80%. ConclusionThere are many risk points and failures for transfusion and infusion warmers, so enterprises should improve processes and quality control to address risks, and medical institutions should formulate specifications and maintenance plans to provide targeted theoretical basis for supervision.